Functional nutrition to support the health of the population of Ukraine under wartime conditions - Stetsenko, Natalia; Simahina, Galina; Goyko, Iryna; Bashta (Sheremet), Alla (My University, 2023)
The population of Ukraine has been living in conditions of Russian aggression for more than a year and is in a state of stress due to shelling, uncertainty of the future, risks of loss of life and property, worries for the lives of relatives who are in the ranks of the defense forces or found themselves in territories temporarily not controlled by Ukraine. Under these conditions, the quality of food, drinking water, and the environment deteriorate, with complex negative impacts on people's health. They need particular special nutrition with a full set of necessary essential nutrients, capable of providing physical and psychological endurance, preventing the occurrence and development of somatic, nervous and other types of various diseases. For this, health and functional food products and drinks are needed, which will include a scientifically based selection of physiologically functional ingredients with the necessary medical and biological indicators and directed therapeutic and preventive properties. The research analyses the positive effects of micronutrients that affect physiological processes in the human body during periods of stress and poststress. It is known that in such conditions the metabolism takes place more actively, the consumption of some vitamins and minerals increases, therefore the need for antioxidant vitamins and vitamin cofactors of the body's enzymatic systems increases. There are a number of factors that increase the impact of stress on the human body and, as a result, should be excluded. These include food toxins, alcohol, oxidants, and free radicals. One of the most promising ways to prevent stress and reduce its consequences is to include functional foods and beverages as part of the diet. Their composition should include these functional ingredients, the deficiency of which disrupts the body's adaptive capabilities.

Населення України понад рік живе в умовах російської агресії та перебуває у стані стресу через обстріли, невизначеність майбутнього, ризики втрати життя та майна, переживання за життя рідних, які знаходяться у лавах сил оборони або опинилися на тимчасово непідконтрольних Україні територіях. За таких умов відбувається зниження якості харчування, питної води, погіршення стану навколишнього середовища, що комплексно негативно відображається на стані здоров’я людей. Вони потребують особливого спеціального харчування з повним набором необхідних есенціальних нутрієнтів, здатних забезпечити фізичну та психологічну витривалість, запобігти виникненню і розвиткові соматичних, нервових та інших видів різноманітних захворювань. Для цього необхідні оздоровчі та функціональні харчові продукти і напої, у складі яких буде науково обґрунтований підбір фізіологічно функціональних інгредієнтів з необхідними медико-біологічними показниками та спрямованими лікувально-профілактичними властивостями. У роботі проведено аналіз позитивної дії мікронутрієнтів, які впливають на фізіологічні процеси в організмі людини у стресовий та післястресовий періоди. Відомо, що в таких умовах обмін речовин відбувається більш активно, зростають витрати деяких вітамінів та мінеральних речовин, тому зростає необхідність у вітамінах-антиоксидантах та вітамінах-кофакторах ферментативних систем організму. Існує низка чинників, які збільшують наслідки стресу для організму людини і тому мають бути виключені. До них належать харчові токсини, алкоголь, оксиданти, вільні радикали. Одним з найбільш перспективних напрямів профілактики стресу та зменшення його наслідків є включення до раціону харчування функціональних харчових продуктів та напоїв. У їх складі мають бути ті функціональні інгредієнти, дефіцит яких порушує адаптаційні можливості організму.
Keywords: functional nutrition; functional food; stress; public health; vitamins; antioxidants; функціональне харчування; функціональний харчовий продукт; стрес; громадське здоров'я; вітаміни; антиоксиданти; кафедра технології оздоровчих продуктів